(untitled) (Journal of Medicine, 2009)
Background: Pregnant ladies are most likely to develop relative iodine deficiency during pregnancy to affect thyroid function in our population unless specific dietary care or therapeutic iodine supplementation is taken into account which is yet to be materialized. Methods: In this cohort study sixty uncomplicated normal pregnant women were enrolled in 1st trimester and followed up till delivery. In every trimester maternal iodine status & thyroid status were determined by urinary iodine & serum thyroid hormone concentration respectively. Results: Women progressively become more iodine deficient & tends to be hypothyroid as pregnancy advances. At 3rd trimester of pregnancy maternal Urinary Iodine found to be negatively correlated with their serum TSH. Conclusion: During pregnancy women develop iodine deficiency which adversely affects the thyroid function. So adequate iodine monitoring and iodine nutrition during pregnancy is necessary. Keywords: Urinary iodine level, TSH, FT3, FT4. doi: 10.3329/jom.v10i2.2815 J MEDICINE 2009; 10 : 56-59